2020
DOI: 10.3390/ijms21062103
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Strategies for the Prevention and Treatment of Distinct Stages of Type 1 Diabetes: An Overview

Abstract: Type 1 diabetes mellitus is a heterogeneous disorder characterized by destruction of pancreatic β cells, culminating in absolute insulin deficiency. The goals of Type 1 diabetes care, established by the Diabetes Control and Complications Trial (DCCT), are to achieve good glycemic control, to prevent hyperglycaemia (which is associated with long-term microvascular and macrovascular complications) and to avoid recurrent episodes of hypoglycaemia (which may have adverse effects on cognitive function). However, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Our RCT is also the longest investigation in PR in an exclusively pediatric population receiving standardized insulin regimen and high dose ergocalciferol. The dose of ergocalciferol used in this study was similar to the dose used in other studies that suggested that higher doses of vitamin D are necessary for the detection of its extra skeletal functions (11,16). The patients' characteristics and the RCT design make the results of the study generalizable to all youth with newly diagnosed T1D given the ethnic and racial diversity, the age range, and the duration of the trial.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Our RCT is also the longest investigation in PR in an exclusively pediatric population receiving standardized insulin regimen and high dose ergocalciferol. The dose of ergocalciferol used in this study was similar to the dose used in other studies that suggested that higher doses of vitamin D are necessary for the detection of its extra skeletal functions (11,16). The patients' characteristics and the RCT design make the results of the study generalizable to all youth with newly diagnosed T1D given the ethnic and racial diversity, the age range, and the duration of the trial.…”
Section: Introductionmentioning
confidence: 79%
“…These include several side effects such as headache, nausea, decreased white blood cell count, and severe rashes. Previous studies that used lower doses of vitamin D had reported unclear results on vitamin D's impact on PR (8,15), thus suggesting that high-dose vitamin D may be necessary to detect vitamin D's extra-skeletal effects in humans (11,16) as has been reported in animal studies (17). Pozzilli and co-workers (18) hypothesized that vitamin D has immunomodulatory functions that favor Th2 immune response that could protect residual b-cells from further destruction following the diagnosis of T1D.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On a general ground the approach based on the use of functionalized lipoplexes we need to remark that this is a personalized gene therapy approach of specific immunocytes. This should avoid side effects of general immunosuppression encountered in trials with MAbs immunotherapeutic approaches such as anti-CD3 ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%